Essential Oils and Hydrolates: Potential Tools for Defense against Bacterial Plant Pathogens - Maria Rita Proto; Enrico Biondi; David Baldo; Matilde Levoni; Gianfranco Filippini; Monica Modesto; Maura Di Vito; Francesca Bugli; Claudio Ratti; Paola Minardi; Paola Mattarelli (Microorganisms, 2022)
The essential oils (EOs) of Origanum compactum and Satureja montana chemotyped (CT) at carvacrol, two Thymus vulgaris CT at thujanol and thymol, and Hydrolates (Hys) of S. montana and Citrus aurantium var. amara were chosen for studying their bactericidal efficacy against few phytobacterial pathogens. The Minimal Inhibitory Concentration (MIC) and Bactericidal Concentration (MBC) were found by microdilution assay. The essential oils of O. compactum (MBC 0.06% v/v), T. vulgaris CT thymol (MBC 0.06% v/v), and Hy of C. aurantium (MBC 6.25% v/v) resulted in being the most effective against Erwinia amylovora; thus, they were used as starting concentrations for ex vivo assays. Despite the great in vitro effectiveness, the disease incidence and the population dynamic ex vivo assays showed no significant results. On the other hand, EO of O. compactum and Hy of C. aurantium (at 0.03% and 4.5% v/v, respectively) showed resistance induction in tomato plants against Xanthomonas vesicatoria infections; both treatments resulted in approximately 50% protection. In conclusion, EOs and Hys could be promising tools for agricultural defense, but further studies will be necessary to stabilize the EOs emulsions, while Hys application could be an effective method to prevent bacterial diseases when used as resistance inducer by pre-transplantation treatment at roots.